2016
DOI: 10.1155/2016/7256496
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of the One-Stage and Two-Stage Impression Techniques: A Comparative Analysis

Abstract: Introduction. One of the main steps of impression is the selection and preparation of an appropriate tray. Hence, the present study aimed to analyze and compare the accuracy of one- and two-stage impression techniques. Materials and Methods. A resin laboratory-made model, as the first molar, was prepared by standard method for full crowns with processed preparation finish line of 1 mm depth and convergence angle of 3-4°. Impression was made 20 times with one-stage technique and 20 times with two-stage techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
(25 reference statements)
0
9
0
1
Order By: Relevance
“…Similarly, another in vitro study evaluated the framework marginal fit (nondestructive technique) and showed that the two-stage impression technique was the most accurate method for VPS impression taking [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, another in vitro study evaluated the framework marginal fit (nondestructive technique) and showed that the two-stage impression technique was the most accurate method for VPS impression taking [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…A wash-bulk thickness of up to 2 mm seems to be an important factor for fabricating an accurate stone dies working model, using VPS impression materials [ 18 , 27 ]. However, there is little information regarding the association between these putty-wash impression techniques and restorations’ marginal fit accuracy [ 28 , 29 ]. The importance and uniqueness of the present in vivo study is that most of the previously reported data originated from in vitro studies.…”
Section: Introductionmentioning
confidence: 99%
“…2,3,4 Pencetakan termasuk proses memindahkan keadaan jaringan lunak dan keras pasien ke laboratorium dan bagian terpenting dalam proses permbuatan gigi tiruan cekat. 5 Tujuan dari pencetakan adalah menciptakan hasil cetakan yang bebas dari cacat pada hasil negatif dari preparasi gigi yang akan memengaruhi akurasi model kerja. Bagian ini penting untuk menghasilkan gigi tiruan memiliki bentuk serta fungsi yang baik.…”
Section: Pendahuluanunclassified
“…The impression phase is predominantly controlled by the clinician and may influence the restoration fit accuracy [8][9][10][11][12]. The impression accuracy is mainly subjected to the effect of proper handling of the impression materials [13][14][15][16][17][18][19] and impression techniques applied [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%